Surface design and stencil: a course for public schools - Morton, Charlene Angusta (My University, 1908)
Introduction: In teaching the principles of color and design to grade students or beginners, we can accomplish very little by giving mere abstract studies, as the average student neither appreciates nor understands them. He should, on the contrary, be encouraged to study some form of applied art, where the underlying principles are plainly evident, yet do not require more skill than he possesses.
Citation: Morton, Charlene Angusta. Surface design and stencil: a course for public schools. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Humanities; Art; Stencils; Education; Graduating theses; Senior theses; Theses